Unusual Variant of Ameloblastoma with Calcifying Epithelial Odontogenic Tumor-like Areas in a Three-Year Old Child - Maryam Fatima; Aribah Atiq; Zubaria Rafique; Faria Khan; Azra Bashir; Omar Chughtai (Journal of University College of Medicine and Dentistry)
The Calcifying Epithelial Odontogenic Tumor (CEOT) is a benign odontogenic tumor, comprising approximately 1% of all odontogenic tumors. It presents as a slow-growing tumor in posterior mandibular region. A three year-old female child from Multan, reported a swelling in right lower jaw progressively increasing in size eventually causing facial asymmetry. On intraoral examination, a protuberance was seen arising from posterior mandibular region and causing displacement of overlying teeth. The swelling was cystic on palpation and mildly tender. The patient underwent complete excision of lesion at a tertiary care center in her locality. The excision biopsy specimen was received at our lab which was intact and well preserved. A diagnosis of ameloblastoma with Calcifying epithelial odontogenic tumor-like areas was made. The patient was followed up after six months however no complaint of any recurrent swelling in the area of was recorded.